The Development of Elderly Emotion by Lanna Folk Music : of Chang-Puek Municipality, Meuang district, Chiang Mai province - นุตสาระ ธนพชร (Community and Social Development Journal, 2018)
The research of the development of elderly emotion by Lanna folk music of Chang-Puek Municipality, Meuang district, Chiang Mai province is mixed method both quantitative, qualitative and experiment research. The aim of this research is to study results of using Lanna folk musical leaning program to develop positive emotion of elderly people. Data of this study is obtained by documents and interviews and research findings will be presented as descriptive analysis and arithmetic mean. Research findings found that ten participants of Lanna folk musical learning program shows positive emotion. Results of Lanna folk musical learning program also reveals that there were 7 elderly women and 3 elderly men, with the age between 65 – 79 years old, their education background is from the 4th grade primary school – bachelor degree, most of them are working as civil servants, private company and general hiring, they also live with their family. Thus, these factors does not affect positive emotion from learning Lanna folk music. For participants who joined the Lanna folk musical learning program, research data shows that before learning, elderly participants have good emotion. And, after learning all participants have enjoyable and edgy emotions but feel excited and proud to play music, as a result of limitations of participants in learning music at the elder age, especially brain controlling of using the left hand to press the wire to create melody and the right hand to pluck and bow. Elderly participants can only do one hand at a time, so, when they need to play music by using both hands together can be very slow, which makes them become irritated. The questionnaire of self-evaluating positive emotion in different situations shows an average value of 4.52-4.96, which is the maximum level.